The 360° performance system in team sports: is it time to design a "personalized jacket" for team sports players? - Jukic, I.; Calleja-Gonzalez, J.; Cuzzolin, F.; Sampaio, J.; Cos, F.; Milanovic, L.; Krakan, I.; Ostojic, S.; Olmo, J.; Requena, B.; Njaradi, N.; Sassi, R.; et al. (Sports, 2021)
Elite performance in team sports attracts the attention of the general public. In particular, the best players became incredibly skilled and physically powerful, which is a fact that potentiates the delivery of a product that is considered attractive, exciting, and competitive. Not surprisingly, this is a very valuable product from an economic and social standpoint; thus, all sports professionals are extremely interested in developing new procedures to improve their sports performance. Furthermore, the great interests of the various stakeholders (owners, chief executive officers (CEOs), agents, fans, media, coaches, players, families, and friends) are one of the main reasons for this development under the sports science umbrella and the accompanying sports industry. All their personal performances should be coordinated and put into practice by the sports team. In this scientific and applied study, we primarily dealt with the individual treatment of players in order to improve their personal performance and, consequently, the team`s sporting performance.